2014
DOI: 10.2967/jnumed.114.146886
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Diffusion-Weighted Imaging in Simultaneous 18F-FDG PET/MR Imaging for Whole-Body Staging of Women with Pelvic Malignancies

Abstract: The aim of this study was to assess the diagnostic benefit of diffusion-weighted imaging (DWI) in an 18 F-FDG PET/MR imaging protocol for whole-body staging of women with primary or recurrent malignancies of the pelvis. Methods: Forty-eight patients with a primary pelvic malignancy or suspected recurrence of a pelvic malignancy were included in our study. All patients underwent a whole-body 18 F-FDG PET/MR imaging examination that included DWI. Two radiologists separately evaluated the PET/MR imaging datasets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…The pooled results of sensitivity, specificity, LR+, LR- and the AUC implied that PET/MRI had an outstanding performance for assessment of metastasis to these sites [26, 34]. These results were in line with the results of studies included in this meta-analysis and previously published data [27, 30]. To achieve the best patient management for gynecological cancers, high-quality imaging technique of early detection and evaluation is essential.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The pooled results of sensitivity, specificity, LR+, LR- and the AUC implied that PET/MRI had an outstanding performance for assessment of metastasis to these sites [26, 34]. These results were in line with the results of studies included in this meta-analysis and previously published data [27, 30]. To achieve the best patient management for gynecological cancers, high-quality imaging technique of early detection and evaluation is essential.…”
Section: Discussionsupporting
confidence: 80%
“…The remaining 145 candidate studies were downloaded and assessed for eligibility, and 138 articles were further removed. Eventually, seven studies were eligible in our research [2733]. There were two authors each one of whom has published three articles, the patient samples of these studies with the same author(s) were not completely same and they presented different data concerning subgroup analysis.…”
Section: Resultsmentioning
confidence: 99%
“…There have several articles examining the utility of PET/MR in thoracic tumors with findings suggesting that FDG PET/MR is superior to FDG PET/CT [67][68][69][70][71]. While there has been promise in the use of whole body diffusion-weighted imaging (DWI) with PET/MR in malignancies such as lymphoma [72], and head and neck cancers [73], one recent study in primary or recurrent gynecologic tumors found DWI did not have any diagnostic benefit for whole-body staging [74] .…”
Section: Gynecologic Malignancymentioning
confidence: 97%
“…For example, in a study of 34 women undergoing whole-body staging for suspected recurrence of cervical or ovarian cancer, FDG PET/MRI accurately identified 98.9% of malignant lesions, compared with 88.8% by MRI alone, and had significantly higher lesion contrast and diagnostic confidence in the detection of malignant lesions compared with MRI alone [71]. In an additional study of 122 suspected lesions in 48 women undergoing staging for gynecologic malignancy, whole-body FDG PET/MRI achieved over 90% accuracy for identification of malignant lesions [72]. …”
Section: Clinical Examplesmentioning
confidence: 99%